Studi Deskriptif Internet Financial Reporting dan Enterprise Risk Management Perusahaan - Gustita Arnawati Putri (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Increasing technological developments require many parties to always adjust to all kinds of changes that will occur in the future, both economic conditions, government regulations, consumer conditions, and conditions of competitors. The way companies communicate with their investors has also changed, as a result of the rapid development of the internet. The internet that companies use to report financial information to investors is called Internet Financial Reporting (IFR). Today, IFR has been put forward by most countries because it can minimize the negative effects of information asymmetry, reduce agency costs, reduce capital costs, and increase firm value. Companies in achieving their goals are faced with uncertain conditions. The purpose of this study is to find out how the differences between IFR and ERM in commercial banks in Indonesia with high and low market capitalization values. This research is a non-static analytical descriptive study. The sample used is only two commercial banks to be compared. The results of the comparative analysis carried out showed that there was no significant difference in the implementation of IFR, but in the implementation of ERM there were significant differences.